Desenvolvimento de comprimidos de liberação prolongada contendo dapsona para tratamento de hanseníase - Kasbaum, Fritz Eduardo (2010)
The present work show the pharmaceutical development of new release systems of drugs, specifically dapsona's (DDS) prolonged release tablets, a sulfon with bacteriostatic action used on the leprosy treatment and several other skin diseases and also in the treatment of the other pathologies as malaria and pneumonia caused by Pneumocystis carinii. This drug, depending on the pathology, can be managed in doses trat vary between 25 to 300m/day, and the administration frequency added to the high doses is responsible for the sprouting of serious collateral effect in the hematologic system, amongst them the methemoglobinemia and in some cases hemolysis. Systems of modified release aim to optimize the medicines therapy by reduction of the usually managed doses, attainment of plasmatic levels more uniforms of the drug for bigger period of time in administrations frequency and also reduction of the observed collateral effect. Eight formulations of DDS were prepared using as excipients the microcrystalline cellulose, the monohydrated lactose spray dryer and magnesium stearate. To compose a matricial system of asset release it was formulated tablets sometimes contending matrix with hydrophilic characteristic and sometimes lipofilic, respectively, hidroxipropilmetilcelulose (HPMC) and gliceril monostearate (MEG). The prepared formulations were submitted to dissolution tests in medium that simulated the stomachal and enteric conditions and the respective profiles or release were evaluated the Kinetic of DDS release to elucidate the mechanisms that controls it. The results of release throughout the time had been treated in accordance with model zero-order, first-order, Higuchi and exponential model. The gotten coefficients of correlation indicate that DDS release from the chosen formulation follows exponential model.